Flesh characteristics: Estimation of genetic parameters and correlated responses to selection for growth rate in the GIFT strain - Hamzah, A.; Nguyen Hong Nguyen; Mekkawy, Wagdy; Ponzoni, R.W.; Hooi Ling Khaw; Hoong Yip Yee; Abu Bakar, Khairul Rizal; Mohd Nor, S.A. (Hindawi Limited, 2016)
Flesh characteristics comprising chemical composition (protein, fat and moisture percentages and pH) as well as a sensory attribute (colour) were measured in 1951 fillet samples from two generations of two populations (a selection line, selected for increased harvest weight, and a control line, selected for average breeding values for harvest weight) of the genetically improved farmed tilapia (GIFT) strain of Nile tilapia. These data were jointly analysed with 5331 harvest weight records from three generations to estimate genetic parameters and correlated selection responses. Multiple trait animal models were used in the analyses. The potential for correlated responses was evaluated by estimating heritabilities and genetic correlations between body traits (weight, length, depth and width) and fillet traits (weight and yield) with the above mentioned flesh characteristics. The heritabilities for protein%, fat% and colour were low (0.06–0.11), whereas for moisture% and pH they were moderate (0.15–0.20). Genetic correlations among some flesh characteristics (moisture% with protein%, fat% and pH and with fat%) as well as between body and fillet traits with flesh characteristics, were significantly different from zero but low (−0.34 to 0.31). Correlated responses were evaluated by comparing the least squares means between the Selection and Control lines. Our results indicate that selection for high growth increased harvest weight in the Selection line relative to the Control line but it did not change the flesh characteristics of the GIFT strain.